Empowering Non-EFL Students' Speaking Skills through E-Portfolios: A Design-Based Research in Primary Teacher Education - Wariyati, Wariyati; Rosly, Rohazlyn; Marisa, Vera; Heridayani, Heridayani (UIN Sumatera Utara, 2025)
English proficiency is essential for global communication across various domains. However, non-EFL students, particularly in Primary Teacher Education Programs, often struggle with speaking skills due to limited vocabulary and low confidence. This study employs a Design-Based Research (DBR) approach to develop and implement an e-portfolio-based assessment aimed at improving students’ speaking abilities. Data were collected from PGSD students at UMN Al Washliyah through observations, interviews, and document analysis. Results indicate significant improvements in four key speaking components: fluency, pronunciation, vocabulary, and grammar. The use of e-portfolios not only enhanced speaking performance but also increased student motivation and engagement.